School subject choices in adolescence affect political party support. - Martin, Nicole S.; Scott, Ralph; Kappe, Roland (West European Politics, 2026)
The educational cleavage is restructuring electoral competition in many democracies, yet there has been insufficient attention on how variation in educational content affects this. In order to address this, this article combines English administrative school records with a unique representative panel of adolescents to estimate the within-individual effect of studying different subjects at school on political party preference. This analysis finds that studying arts and humanities subjects leads to greater support for socially liberal parties, whilst studying business and economics increases support for economically right-wing parties. Students who study technical subjects become more likely to support socially conservative and economically right-wing parties. These relationships between particular subjects and party support also persist into adulthood. As such, this article provides new evidence on the importance of subjects taken in secondary school for political socialisation, during the impressionable years of adolescence.